Proposta de otimização da alocação da antena de transmissão em região rural - Guiotoku, Marcus Paulo Araújo (2006)
The science has achieved such a big development and it has allowed men to break the geographic barriers, in special in the field of communications. One important character in all this evolution is the development of the telecommunications. Nowadays more and more limits are being broken and the telecommunications are leading the men to boundaries never dreamed yet. In this context, this work contributes with a survey about the interdecile-range, or h (the terrain irregularity parameter). This parameter is very used in many empirical prediction models. The survey about Δh covers the Triângulo Mineiro area and other regions. This research also contributes with an optimization proposal of a transmission antenna allocation in rural areas, intending to offer parameters for the choice of the antenna installation place, looking for smaller average loss and bigger coverage area.